2012
DOI: 10.1007/s00125-012-2807-7
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated overexpression of Tcfe3 ameliorates hyperglycaemia in a mouse model of diabetes by upregulating glucokinase in the liver

Abstract: Aims/hypothesis Transcription factor E3 (TFE3) has been shown to increase insulin sensitivity by activating insulinsignalling pathways. However, the role of TFE3 in glucose homeostasis is not fully understood. Here, we explored the possible therapeutic potential of TFE3 for the control of hyperglycaemia using a streptozotocin-induced mouse model of diabetes. Methods We achieved overabundance of TFE3 in streptozotocin mice by administering an adenovirus (Ad) or adenoassociated virus serotype 2 (AAV2). We also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Previous studies using TFE3 transgenic mice showed that TFE3 is capable of activating genes involved in energy metabolism processes including glycolysis and insulin signalling (Nakagawa et al , ; Fujimoto et al , ; Kim et al , ; Xiong et al , ). However, as these studies were limited to overexpression, the physiological role of TFE3 has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using TFE3 transgenic mice showed that TFE3 is capable of activating genes involved in energy metabolism processes including glycolysis and insulin signalling (Nakagawa et al , ; Fujimoto et al , ; Kim et al , ; Xiong et al , ). However, as these studies were limited to overexpression, the physiological role of TFE3 has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Promoter analysis revealed the overexpression of TFE3 could also enhance the expression of hexokinase 2 (HKII) and liver-type glucokinase in hepatocytes. Simultaneously, some studies revealed that these two genes were downstream targets of TFE3 [18,25]. The nuclear receptor, REV-ERBα, is involved in lipid, bile acid, and glucose metabolism in the liver.…”
Section: Tfe3 Can Regulate the Daily Metabolism Of Hepatocytes By Reg...mentioning
confidence: 97%
“…Subsequent to this study, we hypothesized that transcription factor E3 (TFE3) could be able to up-regulate Gck because TFE3 was shown to up-regulate genes of insulin signaling pathway [15]. Using adenoviral transduction of TFE3, we demonstrated the presence of TFE3 binding site (E-box) in the Gck and TFE3 up-regulates Gck with amelioration of hyperglycemia in the db/db and ob/ob mice [16]. Fig.…”
Section: Srebp-1c and Glucose Metabolismmentioning
confidence: 99%